2002
DOI: 10.1074/jbc.m109989200
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Specific Extracellular Antagonism of Receptor-Histidine Kinase Signaling

Abstract: Staphylococcal pathogenesis is regulated by a twocomponent quorum-sensing system, agr, activated by a self-coded autoinducing peptide (AIP). The agr system is widely divergent and is unique in that variant AIPs cross-inhibit agr activation in heterologous combinations. Cross-inhibition, but not self-activation, is widely tolerant of structural diversity in the AIPs so that these two processes must involve different mechanisms of interaction with the respective receptors. Herein, we have utilized this naturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
113
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 23 publications
5
113
0
Order By: Relevance
“…In previous AIP structure-function analyses, agr cross-inhibition was determined to require the AIP ring structure, but it was relatively tolerant of amino acid replacements (6,14), as well as replacement of the thiolactone bond with a lactam (4,13,17). These results suggested that autologous and heterologous AIPs interact with AgrC via unique yet overlapping binding sites, consistent with a process of competitive inhibition.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In previous AIP structure-function analyses, agr cross-inhibition was determined to require the AIP ring structure, but it was relatively tolerant of amino acid replacements (6,14), as well as replacement of the thiolactone bond with a lactam (4,13,17). These results suggested that autologous and heterologous AIPs interact with AgrC via unique yet overlapping binding sites, consistent with a process of competitive inhibition.…”
Section: Discussionmentioning
confidence: 60%
“…Generally, only the cognate ligand-receptor interaction causes activation, whereas most heterologous interactions inhibit the receptor, resulting in a form of bacterial interference directly affecting accessory gene expression. Inhibition by heterologous AIPs is reversible (13), is equivalent in strength to activation (2), and is highly tolerant of AIP sequence variation (2,6,14). agr crossinhibition may drive evolutionary diversification among the staphylococci (11) and has important implications for host infections, because treatment with S. aureus AIP-II was shown to prevent the formation of an experimental murine abscess by agr-I cells (2,15).…”
mentioning
confidence: 99%
“…This may help to explain why residues critical for activity differ between AIP groups. Systematic mutation of native AIP molecules has generated analogues with various changes in activity, including reduced activation activity, enhanced activation activity, loss of all activity, conversion of self-activation to self-inhibition activity, and a unique case of conversion of cross-inhibition to cross-activation activity (218)(219)(220)(221). Combining multiple mutations known to provide antagonist activity, for example, truncating the tail of a selfinhibitory AIP-I mutant, has also been shown to have potential in the generation of stronger inhibitors that function against all agr groups (218).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…The P2 transcript, RNA II, encodes four genes, agrA, B, C, and D (6,7). AgrC, a transmembrane protein, is a sensor kinase of the classic bacterial two component signal transduction system: the N-terminal half is the input domain that interacts with a signal molecule produced by the bacteria, and the C-terminal half is a transmitter that is autophosphorylated at a conserved histidine upon stimulation by the signal molecule (2,13,14). AgrA resembles a response regulator, which is required for the activation of both agr promoters P2 and P3 (2,7,15), although it is not clear whether AgrA binds to these two promoters directly (16,17).…”
mentioning
confidence: 99%